2023
DOI: 10.31234/osf.io/uk7hr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An observational treatment study of metacognition in anxious-depression

Abstract: Objective: Prior studies have found metacognitive impairments are linked to a transdiagnostic dimension of anxious-depression, manifesting as reduced confidence in performance (‘metacognitive bias’). However, previous work has been cross-sectional and so it is unclear if under-confidence is a trait-like marker of anxious-depression vulnerability, or if it resolves when anxious-depression improves.Methods: Data were collected as part of the ‘Precision in Psychiatry’ study, a large-scale transdiagnostic, four-we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…In line with previous research, an anxious-depression (AD) dimension was associated with low confidence in task performance, even in the absence of objective deficits (Benwell et al, 2022;Fox et al, 2023;Hoven et al, 2023;Katyal et al, 2023;Rouault et al, 2018). However, when high AD participants had the chance to increase confidence through seeking additional information, they did not take it more often than those scoring low for AD.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with previous research, an anxious-depression (AD) dimension was associated with low confidence in task performance, even in the absence of objective deficits (Benwell et al, 2022;Fox et al, 2023;Hoven et al, 2023;Katyal et al, 2023;Rouault et al, 2018). However, when high AD participants had the chance to increase confidence through seeking additional information, they did not take it more often than those scoring low for AD.…”
Section: Discussionsupporting
confidence: 85%
“…In line with previous studies (Benwell et al, 2022;Fox et al, 2023;Hoven et al, 2023;Moses-Payne et al, 2019), no relationships surviving multiple comparison correction were found between metacognitive efficiency (meta-d'/d') and any of the symptom dimensions, age, or sex for either the first or final decisions (see Supplementary Figure S3).…”
Section: Information Seeking and Psychiatric Symptom Dimensionssupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with previous studies that found strong between-task correlations of metacognitive bias (Ais et al, 2016;Benwell et al, 2022b;Mazancieux et al, 2020), suggesting overall confidence level is a domain-general, trait-like characteristic that is less influenced by task-specific representations and evidence type. This highlights that maladaptive confidence calibration may have a more pervasive influence on everyday life, in line with its association with symptoms of psychopathology (Benwell et al, 2022b;Rouault, Seow, et al, 2018) and longitudinal evidence of confidence bias improvement with mental health treatment (Fox et al, 2023). Hence, identifying reliable, domain-general EEG predictors of confidence may represent a first step towards understanding neural mechanisms relevant for mental health.…”
Section: Test-retest Reliability and Domain-generality Of Metacogniti...mentioning
confidence: 83%
“…These relationships are observed in both "local" confidence judgments on individual trials [2][3][4] and "global" confidence as measured through long-run self-performance estimates 5 (which we refer to as global SPEs [6][7][8] ). Conversely, remission from depression symptoms, through either therapy or antidepressants, is found to ameliorate underconfidence 9,10 . However, previous studies examining the link between metacognition and symptoms have been descriptive, and a mechanistic understanding of why confidence distortions in anxious-depression persist despite otherwise intact performance remains elusive.…”
Section: Introductionmentioning
confidence: 99%